One-pot generation of benzynes from 2-aminophenylboronates via a Rh(ii)-catalyzed N–H amination/oxidation/elimination cascade process. Issue 1 (18th November 2019) - Ito, Motoki; Tanaka, Arisa; Hatakeyama, Keiju; Kano, Emi; Higuchi, Kazuhiro; Sugiyama, Shigeo
Abstract : Rh(ii )-Nitrene-mediated N–H amination of 2-aminophenylboronates triggered a cascade of oxidation/elimination processes resulting in the generation of benzynes. Abstract : This article describes the first application of 2-aminophenylboronates as precursors for benzynes. Utilizing Rh2 (HNCOCF3 )4 as the catalyst, Rh(ii )-nitrene-mediated N–H amination of the starting material triggered a cascade of oxidation/elimination processes resulting in the generation of benzynes, thus providing suitable conditions for a one-pot cycloaddition with azides or furans. The transformation proceeded under acid-, base-, and fluoride-free conditions, below ambient temperature, and was applicable to a range of substrates containing glycoside and nucleoside moieties, as well as silyl-functional groups.